Efficiency of Arabica Coffee Processing Unit in Ngada Regency - Kornelia Ngina Djawa; Irham Irham; Lestari Rahayu Waluyati (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2019)
Village-based processing unit is a small-scale agricultural processing industry based in rural areas. It is a breakthrough program in accelerating the growth of farmers' income and increased employment. The product processing unit has a goal of obtaining maximum benefit. In order to achieve maximum profit and continuous processing of coffee, the processing unit should pay attention to the efficiency aspect. The purpose of this research is to know the efficiency of the coffee processing unit in Ngada regency and the improvement strategy for processing unit of an inefficient result to be efficient. The analysis method used is Data Envelopment Analysis (DEA) of Charnes, Cooper, and Rhodes (CCR) model and Banker, Charnes, and Cooper (BCC) model with output orientation. The research sample is the management of the coffee processing unit, with the total of 40 respondents. The result of this research shows that the efficiency measurement using DEA method of the CCR model produces coffee processing unit in Ngada regency which efficiently reaches 9 units or 22.5% while 31 or 77.5% other processing units are inefficient. On the BCC model unit, the efficient coffee processing is 20 units or 50%, while the other 20 units or 50% are in the inefficient state. The inefficient processing unit is because the available input is not used optimally. Inefficient processing units can be achieved efficiently by referring to efficient processing units within their peer groups by adjusting the excessive amount of input usage